The Association Between Visceral Obesity and Postoperative Outcomes in Elderly Patients With Colorectal Cancer - Dong, Qiantong; Song, Haonan; Chen, Weizhe; Wang, Wenbin; Ruan, Xiaojiao; Xie, Tingting; Huang, Dongdong; Chen, Xiaolei; Xing, Chungen (Frontiers in Surgery, 2022)
Background The impact of visceral obesity on the postoperative complications of colorectal cancer in elderly patients has not been well studied. This study aims to explore the influence of visceral obesity on surgical outcomes in elderly patients who have accepted a radical surgery for colorectal cancer. Methods Patients aged over 65 year who had undergone colorectal cancer resections from January 2015 to September 2020 were enrolled. Visceral obesity is typically evaluated based on visceral fat area (VFA) which is measured by computed tomography (CT) imaging. Univariate and multivariate analyses were performed to analyze parameters related to short-term outcomes. Results A total of 528 patients participated in this prospective study. Patients with visceral obesity exhibited the higher incidence of total (34.1% vs. 18.0%, P < 0.001), surgical (26.1% vs. 14.6%, P = 0.001) and medical (12.6% vs. 6.7%, P = 0.022) complications. Based on multivariate analysis, visceral obesity and preoperative poorly controlled hypoalbuminemia were considered as independent risk factors for postoperative complications in elderly patients after colorectal cancer surgery. Conclusions Visceral obesity, evaluated by VFA, was a crucial clinical predictor of short-term outcomes after colorectal cancer surgery in elderly patients. More attentions should be paid to these elderly patients before surgery.